ANALISIS PROFIL KEMAMPUAN LITERASI SAINS SISWA SMP/MTs DI KABUPATEN PATI - Nurul Hidayah; Ani Rusilowati; M Masturi (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2019)
The aims of this study to describe the science literacy profile of junior high school students in science learning. The research sample is the students of class IX junior high school in Pati. The research using this descriptive method, data were collected by using science literacy test questions, questionnaires, and interview formats. The results showed that the average achievement of student science literacy as a whole was 28,31%. Ability to explain scientific phenomena of 28.64%, students 'ability in evaluating and designing scientific investigation of 24.48% and students' ability in interpreting data and scientific evidence of 31.81%. This shows that the mean percentage of science literacy on three science literacy capacities measured shows 50%. The low one of the literacy skills of science will affect the ability of other science literacy. Based on the questionnaire analysis used in the research reveals factors that affect the ability of science literacy students include interest in science, learning motivation, teacher strategy in learning, and school facilities.